PENERAPAN MODEL SIKLUS BELAJAR 7E PADA TEMA GLOBAL WARMING UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS VII SMP - Pertiwi, Fiza Dora Selpa (2017)
This study aimed to get description about the implementation of 7E learning cycle model (elicit, engage, explore, explain, elaborate, extend, evaluate) on global warming theme to increase science literacy of grade VII students of SMP. The research method used is quasi experiment with non-equivalent type pretest-posttest control-group design. The research was conducted in class VII of one of junior high school in Bandung, involving 57 students consisting of experimental class (N = 30) and control class (N = 27). Data from preliminary and final tests were used to see the difference in the acquisition of students' science literacy before and after application of the model. The same data is also obtained from the control class. Based on the result of data analysis, the average of n-gain of science experimental class literacy test is 0,48 with medium category and control class 0,28 with low category for knowledge aspect (science content) and competence (science process). The result of t-test and effect size indicates that the increase of science literacy of experiment class is significantly better than control class and has strong effect. Attitude score based on the data analysis result obtained the average of n-gain for experiment class and control class are 0,39 and 0,35 with medium category. It can be concluded that the 7E learning cycle model can increase the science literacy of junior high school students on global warming theme.---- Penelitian ini dilakukan untuk memperoleh deskripsi tentang penerapan model siklus belajar 7E (elicit, engage, explore, explain, elaborate, extend, evaluate) pada tema global warming untuk meningkatkan literasi sains siswa kelas VII SMP. Metode penelitian yang digunakan adalah kuasi eksperimen dengan tipe non-equivalent pretest-posttest control-group design. Penelitian dilaksanakan di kelas VII salah satu SMP di kota Bandung, melibatkan 57 siswa yang terdiri atas kelas eksperimen (N = 30) dan kelas kontrol (N = 27). Data dari tes awal dan tes akhir digunakan untuk melihat perbedaan perolehan literasi sains siswa sebelum dan setelah penerapan model. Data yang sama diperoleh pula dari kelas kontrol. Berdasarkan hasil analisis data diperoleh rata-rata n-gain tes literasi sains kelas eksperimen sebesar 0,48 dengan kategori sedang dan kelas kontrol sebesar 0,28 dengan kategori rendah untuk aspek pengetahuan (konten sains) dan kompetensi (proses sains). Hasil uji-t dan effect size menunjukkan bahwa peningkatan literasi sains kelas eksperimen secara signifikan lebih baik dibandingkan kelas kontrol dan berpengaruh kuat. Skor sikap berdasarkan hasil analisis data diperoleh rata-rata n-gain untuk kelas eksperimen dan kelas kontrol berturut-turut sebesar 0,39 dan 0,35 dengan kategori sedang. Dapat disimpulkan bahwa siklus belajar 7E dapat meningkatkan literasi sains siswa SMP pada tema global warming.